2002
DOI: 10.1007/s10143-001-0197-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography in presurgical epilepsy evaluation

Abstract: The introduction of whole-head magnetoencephalography (MEG) systems facilitating simultaneous recording from the entire brain surface has led to a major breakthrough of MEG in presurgical epilepsy evaluation. Localizations of the interictal spike zone with MEG showed excellent agreement with invasive electrical recordings, were useful to clarify the spatial relationship of the irritative spike zone to structural lesions, and could attribute epileptic activity to lobar subcompartments both in temporal lobe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 113 publications
(173 reference statements)
0
41
0
2
Order By: Relevance
“…We have provided the example of somatosensory processing, but this could readily be extrapolated to more cognitive functions such as attention, language, and emotion, as well as the components typically ascribed to them. For some, this ''reference-dependent'' attribute has been viewed as the principal shortcoming of EEG versus magnetoencephalography (MEG; [50,69,70]). However, as will be shown throughout this tutorial and elsewhere in this special issue [55], alternative and easy-touse analyses can be performed on EEG/ERP data (as well as MEG/MEF data) that do allow researchers to address fundamental neurophysiologic questions.…”
Section: Waveform Analyses: Limitations and Pitfallsmentioning
confidence: 99%
“…We have provided the example of somatosensory processing, but this could readily be extrapolated to more cognitive functions such as attention, language, and emotion, as well as the components typically ascribed to them. For some, this ''reference-dependent'' attribute has been viewed as the principal shortcoming of EEG versus magnetoencephalography (MEG; [50,69,70]). However, as will be shown throughout this tutorial and elsewhere in this special issue [55], alternative and easy-touse analyses can be performed on EEG/ERP data (as well as MEG/MEF data) that do allow researchers to address fundamental neurophysiologic questions.…”
Section: Waveform Analyses: Limitations and Pitfallsmentioning
confidence: 99%
“…The question of the correct reference electrode has been intensively debated in the literature Gencer et al, 1996;Junghofer et al, 1999;Pascual-Marqui and Lehmann, 1993;Tomberg et al, 1990]. And the reference-problem has been taken as a major disadvantage of EEG versus MEG [Pataraia et al, 2002;Wikswo et al, 1993;Williamson et al, 1991]. Yet, many studies have shown that-while the choice of the reference heavily influences waveform analysis-it is actually irrelevant for the analysis of topographic maps (as done in the present study) and for source localization (as done in the present study) as long as the reference is correctly included in the model.…”
Section: Eeg Recordingmentioning
confidence: 99%
“…Synchronized neuronal currents induce weak magnetic fields that can be detected with multichannel sensors placed over the patient' s scalp (9)(10)(11). Superconducting quantum inference devices (SQUIDS) allow detection of small cortical field differences and large shielded rooms cooled by liquid helium and are used to minimize distortion of signal from outside magnetic fields.…”
Section: Magnetoencephalographymentioning
confidence: 99%
“…Mathematical models infer the location of signal generators on the cortex, overlaying them on synchronized MR images. Magnetoencephalography (MEG) has been utilized in localization of seizure foci, language centers, and primary somatosensory cortices (9)(10)(11). One technique involves placement of standard fiducial markers on the patient' s scalp, completion of an MRI, and integration of MRI and MEG studies, yielding a magnetic source image (MSI), that can be integrated with standard intraoperative navigation systems.…”
Section: Magnetoencephalographymentioning
confidence: 99%